PENGAWASAN PASAR MODAL SETELAH BERLAKUNYA UNDANGUNDANG NOMOR 21 TAHUN 2011 TENTANG OTORITAS JASA KEUANGAN - Suwardi (Legalita, 2019)
The capital market is seen as an effective means to accelerate the development of a country because of its ability to mobilize long-term funds from the public to be channeled to productive sectors. However, trading traffic on the capital market requires supervision from the government or parties that are considered to be independent to create safe and comfortable market conditions for each party that will carry out the transaction. This article raises the issue of how to control the capital market before and after the enactment of the Law Number 21 of 2011 concerning the Financial Services Authority ?. The writing of this article uses a normative approach in analyzing various laws and regulations as well as literature related to capital market developments. The process of data analysis is done qualitatively. The function of the capital market supervision after the enactment of Law Number 21 of 2011 concerning OJK replaces the function previously performed by the Capital Market Supervisory Agency (Bapepam). Supervision under the OJK is based on a passion to give attention to protection and education for consumers. Education and protection of financial consumers is directed to increase the trust of investors and consumers in every activity and business activity in the financial services sector and provide opportunities and opportunities for the development of the financial services sector in a fair, efficient and transparent manner.